The response of muscle protein synthesis following whole‐body resistance exercise is greater following 40 g than 20 g of ingested whey protein. Issue 15 (10th August 2016) - Macnaughton, Lindsay S.; Wardle, Sophie L.; Witard, Oliver C.; McGlory, Chris; Hamilton, D. Lee; Jeromson, Stewart; Lawrence, Clare E.; Wallis, Gareth A.; Tipton, Kevin D.
Abstract: The currently accepted amount of protein required to achieve maximal stimulation of myofibrillar protein synthesis (MPS) following resistance exercise is 20–25 g. However, the influence of lean body mass (LBM) on the response of MPS to protein ingestion is unclear. Our aim was to assess the influence of LBM, both total and the amount activated during exercise, on the maximal response of MPS to ingestion of 20 or 40 g of whey protein following a bout of whole‐body resistance exercise. Resistance‐trained males were assigned to a group with lower LBM (≤65 kg; LLBM n  = 15) or higher LBM (≥70 kg; HLBM n  = 15) and participated in two trials in random order. MPS was measured with the infusion of 13 C6‐ phenylalanine tracer and collection of muscle biopsies following ingestion of either 20 or 40 g protein during recovery from a single bout of whole‐body resistance exercise. A similar response of MPS during exercise recovery was observed between LBM groups following protein ingestion (20 g – LLBM: 0.048 ± 0.018%·h −1 ; HLBM: 0.051 ± 0.014%·h −1 ; 40 g – LLBM: 0.059 ± 0.021%·h −1 ; HLBM: 0.059 ± 0.012%·h −1 ). Overall (groups combined), MPS was stimulated to a greater extent following ingestion of 40 g (0.059 ± 0.020%·h −1 ) compared with 20 g (0.049 ± 0.020%·h −1 ; P  = 0.005) of protein. Our data indicate that ingestion of 40 g whey protein following whole‐body resistance exercise stimulates a greater MPS response than 20 g in young resistance‐trained men. However, with the current doses, the total amount of LBM does not seem to influence the response. Abstract : We aimed to determine the influence of lean body mass on the response of muscle protein synthesis to protein ingestion following resistance exercise. The response of muscle protein synthesis following whole body resistance exercise is greater with ingestion of 40 g versus 20 g of whey protein in young, resistance‐trained men.